Incidence of Congenital Abnormalities in Newborn Crossbred Calves - Radjendran, Abarna; Roshini, S Tina; Gurunathan , N; Vigneswari, M; Arrivukkarasi, N; Chimithi, C; Jothi, N Arul (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present study was conducted to know the incidence of common congenital anomalies in calves presented to the Department of Veterinary Surgery and Radiology, RIVER, Puducherry during the period of 2021-2023. A total of 50 calves from day-old to 20 days old were reported with various conditions involving the gastrointestinal system 23 (46.0%), musculoskeletal system 20 (40.0%), urogenital system 4 (8.0%), nervous system 1 (2.0%) and congenital tumors 2 (4.0%). Gastrointestinal disorders included atresia ani, atresia ani et coli, lateral hernia, evisceration of intestine and umbilical hernia. Musculoskeletal disorders included arthrogryposis, contracted tendon, polymelia and prognathism. Nervous system disorders included hydrocephalus. Urogenital system included persistent urachus and atresia ani with ectopic bladder. Congenital tumors reported were vulval growth and congenital melanoma. In this study gastrointestinal system abnormalities were the most frequent among these congenital malformations in crossbred calves.